Registry Data May Prove Useful in Benchmarking Lumbar Spine Surgery Outcomes - Vinall, Phil (MD Conference Express, 2015)
This article presents data from the Swedish Spine Register [Swespine; www.4s.nu] where >90000 surgeries are currently included. Swespine was created >20 years ago and now registers >85% of all lumbar spine surgeries performed in Sweden.